Assessing the Financialization Hypothesis - Fattouh, B; Mahadeva, L (Oxford Institute for Energy Studies, 2012)
The main objectives of this paper are to assess whether financialization can impact oil market behaviour over and above structural fundamental changes, and whether these changes affect final consumers’ welfare. While shifts arising in financial investors’ preferences and wealth can explain the rise in participation of purely financial investors, they fail to explain key features such as the movements in the basis. Instead, anticipated changes in the physical layer of the oil market can better explain many of the features often attributed to financialization. We also find that greater financialization has no harmful effects on consumer welfare. Our paper shows that from a regulatory point of view, it is crucial in the first instance to identify the channels through which financialization can result in market failure and then design policies accordingly.